Investigation of Wave Propagation to PV-Solar Panel Due to Lightning Induced Overvoltage - Nur Hidayu Abdul Rahim; Zikri Abadi Baharudin; Md Nazri Othman; Zahriladha Zakaria; Mohd Shahril Ahmad Khiar; Nur Zawani Saharuddin; Azlinda Ahmad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Lightning produces extremely high voltages that generated induce overvoltage which have a high tendency to effect the electrical apparatus especially renewable energy plant that directly expose to this source. This study was performed through experimental work by investigating the effect of induce overvoltage upon the photovoltaic system. The induce voltage was performed by using lightning impulse generator. It is found that the maximum voltage of the unwanted signal is proportional with the distant of the specimen. The closer distant between solar panel material and spark discharge, the more serious effect would occur due to the induced overvoltage.